Evaluation of photosensitivity based on phototesting in rosacea patients – a retrospective study - Misiak-Gałązka, Magdalena; Wolska, Hanna (Dermatology Review/Przegląd Dermatologiczny, 2012)
Introduction . The etiology and pathogenesis of rosacea are not fully understood. Among factors suspected of inducing and/or exacerbating the skin changes are UV radiation, hormonal changes, stress, alcohol consumption and Demodex folliculorum or Helicobacter pylori infection. There is a general consensus that rosacea is at least a photoaggravated dermatosis. However, several studies in rosacea patients have failed to demonstrate an abnormal reaction to UV radiation. Objective . Retrospective analysis of phototest results in rosacea patients. Material and methods . Retrospective analysis of 102 phototests in rosacea patients with skin types I-III was performed in the Photobiological Laboratory of the Dermatological Department of Warsaw Medical University in the years 2005-2010. As a control results of phototests performed in 56 healthy persons with skin types I-III were used. Results . Decreased MED (≤ 0.047 J/cm 2 ) was found in 34/102 (33.3%) rosacea patients in comparison to 5% in the control group. In the whole group of rosacea patients in comparison to controls a shift into lowered MED was observed (p < 0.0001). Abnormal reactions to UVB radiation (in dose ≤ 2 MED) were evident as vivid, persistent erythema or oedema within the irradiated skin in 20/102 (19.6%) patients (95% CI ±7.8%) (p < 0.0001). Conclusions . The results of our work confirm the role of UV radiation in the pathogenesis of rosacea. Thus, future prospective analysis should evaluate the characteristic features of rosacea patients who are most sensitive to UV radiation.